Endoscopic Ultrasound–Directed Transgastric Endoscopic Retrograde Cholangiopancreatography for Removal of Cystic Duct Coils: A Novel Application of an Emerging Technique. Issue 5 (14th May 2021) - Parvataneni, Swetha; Kumar, Vikas S.; Khan, Yakub I.; Deivert, Duane E.; Obuch, Joshua; Khara, Harshit S.
ABSTRACT: The altered anatomy of patients after Roux-en-Y gastric bypass (RYGB) surgery creates technical challenges for endoscopic and surgical treatment of gallstones. We present a unique case of a post-RYGB patient with complicated gallbladder surgery requiring coiling and embolization of the cystic duct for bile leak. The cystic duct coils migrated out into the bile duct forming a nidus for infection and biliary obstruction, which was resolved using the novel endoscopic ultrasound–directed transgastric routine endoscopic retrograde cholangiopancreatography technique, with successful transpapillary removal of cystic duct coils in RYGB anatomy.